Pengaruh penggunaan pendekatan konstruktivisme terhadap kemampuan berpikir kritis matematik mahasiswa - Depi Setialesmana (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2016)
This study aimed to determine the positive influence of constructivist approach to students’ mathematical critical thinking skills and to investigate the students’ attitude towards the use of a constructivist approach. Population in this study were all students of 2014 batch of economic education, Faculty of Teacher Training and Education, Siliwangi University. The sample used was purposive random sampling for consideration, taken two class of five existing classes. One class was class D become an experimental class that used a constructivist approach and the other class was class B become control class using conventional learning model. Data in this study were taken through the test of critical thinking skills and attitude questionnaires that were given in the experimental class. Data were analysed by the average difference test and attitude scale. The results showed a positive effect of the use of constructivism approach toward students’ mathematical critical thinking skills and students showed a positive attitude to the use of a constructivist approach.